Assessment of Smoking Habits, Oral Hygiene Practices and Perceived Malodour among the College Students in Ahmadabad: Assessment of Smoking Habits, Oral Hygiene Practices and Perceived Malodour among the College Students - Trivedi, Aumkar; Patel, Jalark; Parmar, Mayur; Patel, Soham; Patel, Sapan; Shah, Foram (National Journal of Integrated Research in Medicine, 2018)
Introduction: Halitosis or oral malodour affects a large proportion of the population and is often associated with poor oral hygiene practices, smoking habits, oral and systemic diseases. Objectives: To assess the effect of smoking habits, oral hygiene practices on halitosis and even to evaluate self perceived malodour among college community in Ahmadabad. Methods: A survey was carried out in a college community of Arts and Science students in Ahmadabad, Chennai in order to assess smoking habits, oral hygiene practices and self perceived malodour. All the 1200 students were invited to participate in the study but only 650 volunteers participated and a self administered close ended questionnaire was distributed. Descriptive statistics were used to describe the data. Results: Out of 650 students, only 31 (4.8%) had a habit of smoking and 619 (95.2%) were aware of the ill effects of smoking. 464 (71.3%) brushed once daily, 326 (50 %), 457(70.3%) rinsed their mouth after eating anything and self perceived malodour was expressed by 59(9%). Conclusion: The habit of smoking was seen in a very small percentage of study subjects and majority of them were aware of its ill effects. There is a need to educate them on brushing techniques and encourage them to visit a physician/dentist whenever they perceive a malodour.